Dynamics of gas components during the thermal decomposition process in the pyrolysis of CHangent coal from the Uzgen coal basin and kyrgyz (walnut) coal (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article investigates the changes in the gas-phase components (CO₂, CnHm, CO, H₂S, CH₄) depending on temperature and decomposition time during the pyrolysis of Changent stone coal from the Uzgen coal basin and Kyrgyz (walnut) shell coal. The composition of gases was determined using SIGNAL-N and SIGNAL-EM gas analyzers within the temperature range of 300–800°C and at time intervals of 0.3–1.0 seconds. According to the obtained data, CO₂ and CH₄ gases predominated mainly at low and medium temperatures, while the concentrations of H₂S and CO increased with rising temperature. Hydrocarbons (CnHm) actively accumulated in the medium-temperature region and began to decrease at higher temperatures. The results provide valuable information for the efficient utilization of gaseous products from coal pyrolysis and the optimization of technological parameters.
Keywords: Changent coal, Kyrgyz walnut, pyrolysis, gas composition, CO₂, CH₄, H₂S, temperature regime